Counting Archives In: The Appraisal of the 1991 Census of Canada - Piché, Jean-Stéphen; Powell, Sheila (Archivaria, 1998)
This article is a detailed study of the circumstances, methodology, and findings of the National Archives of Canada's archival appraisal of the data resulting from the 1991 Census of Canada. The authors provide an analysis of the census data - in both anonymized and name identified form - in paper, microfilm, and electronic media. Through their research into the creation and uses of demographic data, the collection of census data from Canadians, and the manipulation of the data by Statistics Canada to render it valid for statistical use, the authors determined that it was necessary to preserve the name identified data provided on census forms by individual Canadians, the anonymized data that is made widely-available for research by Statistics Canada, and evidence of the changes made to the data by Statistics Canada in order to render it statistically "clean." The authors conclude with a discussion of their final appraisal recommendations and the agreement reached between the National Archives of Canada and Statistics Canada to preserve data. RÉSUMÉ Cet article est une étude détaillée des circonstances, de la méthodologie et des conclusions de l'évaluation archivistique des données du Recensement du Canada de 1991 réalisée par les Archives nationales du Canada. Les auteurs analysent les données du recensement -- sous forme anonyme et nominative -- sur papier, microfilm et support informatique. Grâce à leurs recherches sur la création et l'utilisation des données démographiques, sur la collecte des données de recensement auprès des Canadiens et sur la manipulation des informations par Statistique Canada en vue de les rendre valides à des fins statistiques, les auteurs ont déterminé qu'il était nécessaire de préserver à la fois les données nominatives fournies par chaque Canadien sur les questionnaires de recensement, la version anonyme des données que Statistique Canada rend publique pour fins de recherche ainsi que la consignation des modifications apportées aux données. Les auteurs présentent, en conclusion, les recommandations finales de leur évaluation archivistique et l'entente intervenue entre les Archives nationales du Canada et Statistique Canada pour assurer la sauvegarde de ces données.